PERAN GURU PENDIDIKAN AGAMA KATOLIK DALAM MEMBENTUK KARAKTER RELIGIUS SISWA KELAS VII - Fui, Gloria Anita Venesta Opini; Lega, Frans Sales (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2025)
Religious character is one of the essential traits that students must possess, as outlined in the aims of Indonesian national education. This study observes that the formation of students' religious character is closely linked to the role of religious education teachers. Specifically, this research examines the role of Catholic religious education teachers in shaping students' religious character. The central research question is: What is the role of Catholic religious education teachers in shaping the religious character of Grade VII students at SMP Santo Aloysius Turi? To answer this question, a qualitative descriptive research design was employed. The study was conducted at SMPK Santo Aloysius Turi, Sleman Regency, Yogyakarta, with data collected from November to December 2023. The research involved 10 informants: 2 Catholic religious education teachers and 8 Grade VII students. Data were gathered through interviews. The findings show that Catholic religious education teachers at SMP Aloysius Turi have fulfilled their roles in shaping students' religious character through their functions as teachers, educators, role models, mentors, leaders, motivators, learning resources, and facilitators. Religious character values such as faith, honesty, and tolerance are cultivated through both classroom-based (intracurricular) and extracurricular activities. The study concludes that Catholic religious education teachers play a significant and strategic role in fostering students' religious character.